The Use of the Putri Pukes Legend as a Local History Learning Resource for Sixth-Grade Students at SD Negeri 9 Lut Tawar - Amanda, Arizka; Handoko, Handoko (Honoli of Journal Primary Teacher Education, 2026)
History learning in elementary schools tends to be informative and memorization-oriented, making it less contextual and meaningful for students. This study aims to analyze the cultural values, symbolic meanings, and pedagogical potential of the Putri Pukes legend as a local history learning resource. Employing a qualitative approach with a descriptive design, the research was conducted at SD Negeri 9 Lut Tawar, involving sixth-grade students as subjects. Data were collected through documentary study and literature review of the Putri Pukes legend text and relevant scholarly sources, then analyzed using content analysis techniques through the stages of reduction, categorization, and interpretation. The findings show that the Putri Pukes legend contains cultural values reflecting the life of the Gayo people such as obedience to parents, responsibility, patience, sacrifice, and the relationship between humans and nature while also carrying symbolic meanings that represent collective memory and the community's interpretation of the past. Pedagogically, the legend has the potential to serve as a local history learning resource that helps students understand historical material more contextually and develops their historical empathy and imagination. Accordingly, the Putri Pukes legend functions not only as cultural heritage but also as a relevant learning medium for history education in elementary schools.